Intertidal rockpool icthyofauna of El Pital, La Libertad, El Salvador - Saúl González-Murcia; Cindy Marín-Martínez; Arturo Ayala-Bocos (Check List, 2012)
The composition of the rockpool fish community of El Pital was described. A total of 29 rockpools with volumes ranging from 0.12 to 0.83 m3 were sampled from March to September 2009 using dip nets and clove oil anesthetic solution. A total of 106 fishes belonging to 19 species were captured. The most abundant species were Bathygobius ramosus, Abudefduf concolor, Mugil curema and Mugil hospes, representing 66% of all fishes collected. Resident fish comprised 32%, transients comprised 60%, and accidental visitors comprised 8%. High percentages of juvenile fish were recorded (87%), showing that the intertidal zone may act as an important nursery site for fish.